2009
DOI: 10.1103/physreva.79.052339
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the geometrical edges of nonlocal two-qubit gates

Abstract: Nonlocal two-qubit gates are geometrically represented by tetrahedron known as Weyl chamber within which perfect entanglers form a polyhedron. We identify that all edges of the Weyl chamber and polyhedron are formed by single parametric gates. Nonlocal attributes of these edges are characterized using entangling power and local invariants. In particular, SWAP -α family of gates with 1 0 ≤ ≤ α constitutes one edge of the Weyl chamber with SWAP -1/2 being the only perfect entangler.Finally, optimal constructions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…In our earlier study on the geometrical edges of polyhedron, it was shown that for the edges QP, MN and PN [6]. In terms of Eq.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier study on the geometrical edges of polyhedron, it was shown that for the edges QP, MN and PN [6]. In terms of Eq.…”
mentioning
confidence: 99%
“…From our earlier study on the geometrical edges of two-qubit gates [6], it was found that gates which do not belong to the preceding category also possess same entangling power. For 2 example, entangling power of the gates lying in the polyhedron edges QP, MN and PN are identical [6]. Motivated by this fact, here we investigate the entangling power of two-qubit gates in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From this relation, it is clear that the gates having the same and must necessarily possess the same 8 linear entropy, implying that the gates are equally entangled. For example, the edges QP and MN of polyhedron are such that their and are the same [13], resulting in the same linear entropy. Further, the above expression also facilitates to understand the operator entanglement of perfect entanglers.…”
Section: Linear Entropy and Local Invariantsmentioning
confidence: 99%
“…Moreover, the entangling capability of U (C 0 ) can be quantified by the entangling power [31], which is evaluated as [32,33] …”
Section: Fig 3 (Color Online)mentioning
confidence: 99%